ANALYSIS OF PREPAID ELECTRICITY MARKETING COMMUNICATION STRATEGY IN THE ERA OF PANDEMI COVID 19 IN WORKING AREAS PT. PLN (Persero) CUSTOMER SERVICE UNIT (CSU) CIBADAK SUKABUMI - Fadjar Hilmawan; Acep Samsudin; R Deni Muhammad Danial (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The purpose of this study were (1). To give you an idea of how models of Marketing Communication Strategies used PT. PLN (Persero) Customer Service Unit Cibadak Sukabumi Prepaid Electric Program. (2). To find out the factor and factor inhibitors Marketing Communication Strategy Supporting the use PT. PLN (Persero) Customer Service Unit Cibadak Sukabumi Prepaid Electric Program. This study uses descriptive qualitative method. Data from this study were obtained by performing Inteview, observation and documentation. Development of the validity of the data in this study was done by using triangulation. Triangulation techniques used in this study were triangulation, triangulation of data sources and time triangulation. The results obtained are: (1). Electricity Programme Prepaid socializing, PT. PLN (Persero) Customer Service Unit Cibadak Sukabumi, using the Model of Marketing Communications Strategy include: Sender (Source/Sender). Enconding (Translation), The transmission, decoding (Respond and intrepetasi), Action and Feedback. By utilizing direct marketing communications media, and not directly. This direct communication includes several programs related to information and dissemination of Prepaid Electricity Program, the Program Through SARLING (Marketing Roving), cooperation with local or central government, and Person to Person or from the mouth of the mouth. While no direct communication, we use the media covering Promotion Mix Advertising, Sales Promotion, Personal Selling, and Digital Online Marketing. (2). In this socialization is the limiting factor is the lack of public knowledge of the system to change the current information system, and the lack of public response to a change. While supporting factor is the support of the central government, local, and community leaders in the socialization process petrified.